(untitled) (ACME, 2016)
My intention here is to explore the connection between the Garnett family and Stepniak, to call attention to certain aspects of their literary collaboration and to shed light on the offshoots this Anglo-Russian exchange had in modernist fiction, particularly in Virginia Woolf’s prose